ENHANCING EDUCATION QUALITY IN ISLAMIC INSTITUTIONS THROUGH MANAGEMENT APPROACHES - Sodikin, Mohamad; Anto, Parmuji; Anwar, Khoirul (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2024)
Islamic Education Management (IEM) involves the planning, implementation, organization, and evaluation of concepts or theories implemented to enhance the quality of Islamic educational institutions. Several Islamic educational institutions face various challenges in managing their education, including but not limited to limited resources, technological changes, and shifts in labor market demands. Therefore, an innovative and quality-oriented management approach is required to improve the effectiveness and relevance of Islamic education in coping with the dynamics of the time. This research employs a qualitative approach, utilizing existing theories and research findings. This research is initiated with the aim of investigating and analyzing various management approaches that can be used to improve the quality of education in Islamic institutions. It is expected that with this method, research findings can enhance understanding related to Islamic education management. In conlcucion, Islamic Education Management (IEM) plays a pivotal role in addressing the multifaceted challenges faced by Islamic educational institutions. Strategic management emerges as a crucial aspect, involving planning, implementation, and evaluation. Through strategic planning, Islamic educational institutions can set a vision, mission, and goals that align with Islamic values, fostering the development of a strong foundation for IEI. Implementation ensures that these strategies are effectively put into practice, and continuous evaluation guarantees that they contribute positively to the enhancement of Islamic education quality.